Moral Economy and Islamic Ethics: Re-examining Waqf in the Context of Modern Capitalism - Adamu Abubakar Muhammad; Shafa'at Ahmad Aliyu; Ikilima Abubakar Shariff; Rabi Shehu Dalhatu (IDRIS Darulfunun Institute, 2025)
This study investigates the relevance, transformation, and potential revival of waqf (Islamic endowment) as a foundation for moral economy and Islamic ethics in the context of modern capitalism. While traditional Islamic moral economics focuses on equitable wealth distribution and social welfare, current capitalist institutions frequently favor profit maximization, financialization, and market efficiency. This study looks critically at how waqf has historically reduced socioeconomic gaps and how its ideas might be used in modern economic systems to alleviate poverty, social exclusion, and market failures. The paper proposes a normative framework for incorporating waqf into ethical economic strategies that reconcile moral imperatives with capitalist realities, based on doctrinal analysis of Islamic legal texts, a review of contemporary scholarship on moral economy theory, and case studies of modern waqf initiatives. The findings suggest that waqf can serve as a long-term tool for community investment, social safety nets, and value-based economic resilience if legal reform, governance innovation, and ethical institutional frameworks are achieved. The article concludes by advocating policy and institutional options for reviving waqf within global economic systems while maintaining Islamic ethical integrity and modern market efficiency.